Posted by **Aubrey** on Friday, March 16, 2007 at 10:46am.

Convert the simplified parabolic equation y=3x^2-30x-7 to standard form.

3x^2-30x-7

3x^2 -30 x -7 +75 -75

3(x^2 -10x + 25) -82

3(x-5)^2 -82

or

y = 3(x-5)^2 -82

check that.

Thursday

March 23, 2017
Posted by **Aubrey** on Friday, March 16, 2007 at 10:46am.

Convert the simplified parabolic equation y=3x^2-30x-7 to standard form.

3x^2-30x-7

3x^2 -30 x -7 +75 -75

3(x^2 -10x + 25) -82

3(x-5)^2 -82

or

y = 3(x-5)^2 -82

check that.

Search